PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN 21, DAN PPN PADA BISNIS CAFE X - Putri, Tiara Mardiyah; Alis, Selly Maulida Fitri; Putri, Meylani Henni; Silmi, Silmi (Ensiklopedia Sosial Review, 2024)
Taxes are a source of state revenue that comes from people's participation. The state has the authority to collect taxes from the people, because taxes are used to improve the welfare of the people. Tax awareness for taxpayers is very necessary for the state to meet the needs of its people. One of the taxes related to the cafe business is firstly income tax 21 which is subject to withholding of employee income, and secondly value added tax which is tax which is subject to withholding which is charged to buyers or consumers. This research aims to provide knowledge to café owners regarding tax regulations in the form of tax calculations and reporting. The method used is through data collection in the form of interviews from cafe owners. The results of this research aim to show the calculation and method of reporting income tax 21, tax and value added tax.